Orpheus Ascending The Berlin Wall Café by Paul Durcan - Mahon, Derek (ABEI Journal, 2020)
"Orpheus Ascending The Berlin Wall Café by Paul Durcan", by Derek Mahon. The Irish Review, 1986 Published with the kind permission of Gallery Press.